Women, shadows and queens in Emilio Fernandez' movie - Tuñon, Julia (Locus: Revista de História, 2003)
Emilio Fernandez was one of the most important directors in the history of Mexican cinema in the 1940's. We can say that his movies created a stereotype of Mexico and Mexicans built upon love relationships between men and women. This text analyzes the gender relation represented in his movie images.